2010
DOI: 10.1093/annonc/mdq065
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of bevacizumab, oxaliplatin, and docetaxel in locally advanced and metastatic gastric and gastroesophageal junction cancers

Abstract: The combination of bevacizumab, docetaxel, and oxaliplatin has promising activity for further evaluation in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Bevacizumab in combination with 5-fluorouracilbased chemotherapy has been approved as first/second line therapy for advanced colorectal cancer (CRC) and in combination with carboplatin and/or paclitaxel has been approved as first line therapy for advanced non-small cell lung cancer (NSCLC). [18][19][20][21] The success of bevacizumab can be attributed to its sustained target inhibition resulted from its long half-life and good safety profile due to its high specificity allowing it to combine with a variety of chemotherapies. However, bevacizumab has its limitations in the clinic, such as its intravenous dosing, immunogenicity and potential to induce autoimmune diseases after long term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab in combination with 5-fluorouracilbased chemotherapy has been approved as first/second line therapy for advanced colorectal cancer (CRC) and in combination with carboplatin and/or paclitaxel has been approved as first line therapy for advanced non-small cell lung cancer (NSCLC). [18][19][20][21] The success of bevacizumab can be attributed to its sustained target inhibition resulted from its long half-life and good safety profile due to its high specificity allowing it to combine with a variety of chemotherapies. However, bevacizumab has its limitations in the clinic, such as its intravenous dosing, immunogenicity and potential to induce autoimmune diseases after long term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, a further phase II study reported more modest efficacy in combination with oxaliplatin and docetaxel [65], comparable with the results with chemotherapy triplet regimens in phase III studies [10,11]. Unfortunately, these results reflect those reported in the international, randomized phase III AVAGAST (Avastin for Advanced Gastric Cancer) study, in which 774 patients with advanced gastric or esophagogastric junction (EGJ) adenocarcinoma were randomized to a cisplatin-fluoropyrimidine doublet with bevacizumab or placebo in just 14 months.…”
Section: Clinical Data In Esophagogastric Cancer Monoclonal Antibodiementioning
confidence: 56%
“…In contrast to these results, El-Rayes et al reported less efficacy of the addition of bevacizumab to the chemotherapy regimen with docetaxel and oxaliplatin in 38 previously untreated patients with locally advanced or metastatic disease [38]. The disease control rate (DCR) was 79 % with 6.6 months of PFS and 11.1 months of OS.…”
Section: Bevacizumabmentioning
confidence: 91%